PENGARUH EDUKASI SADARI DENGAN METODE DEMOSTRASI TERHADAP PERUBAHAN KEMAMPUAN REMAJA PUTRI MELAKUKAN DETEKSI DINI TUMOR PAYUDARA DI MA AL-MUBAROK BANDAR MATARAM - winarsih wina; Herdini Widyaning Pertiwi; Sulis Julia Wati (STIKES Estu Utomo, 2024)
Background: Data from the World Health Organization, Breast cancer shows the most common cases of cancer. In women with breast cancer cases, it has a percentage of 30.9% with 58,256 of the total cases of 348,809 and a total of 207,210 death cases (World Health Organization, 2020) (Suiganda eit al., 2021) Purpose: This study aims to determine the effect of SADARI education (breast self-examination) with a demonstration method on changes in the ability of adolescent girls to conduct early detection of breast tumors at MA AL-MUBAROK Bandar Mataram. Methods: The design of this research is by quasi experiment design. This research design uses one group pretest - posttest, with a sample of 66 people taken by the Probability Sampling method. Observation is carried out within 1 day. Data collection techniques with direct observation / participatory observation methods Results: From the results of using the Statistical Package for the Social Science (SPSS) program. Bivariate analysis using Wilcoxon's ign rank test showed the influence of BSE examination counseling on BSE knowledge in adolescent girls at MA Al-Mubarok Bandar Mataram with statistical test results obtained p-value 0.000 < ? <0.05 Conclusion: there is an influence of SADARI education with demonstration methods on changes in the ability of adolescent girls to detect early breast tumors